The role of bacteriophages in periodontal health and disease. (October 2016) - Pinto, Graça; Silva, Maria Daniela; Peddey, Mark; Sillankorva, Sanna; Azeredo, Joana
The human periodontium health is commonly compromised by chronic inflammatory conditions and has become a major public health concern. Dental plaque, the precursor of periodontal disease, is a complex biofilm consisting mainly of bacteria, but also archaea, protozoa, fungi and viruses. Viruses that specifically infect bacteria – bacteriophages – are most common in the oral cavity. Despite this, their role in the progression of periodontal disease remains poorly explored. This review aims to summarize how bacteriophages interact with the oral microbiota, their ability to increase bacterial virulence and mediate the transfer of resistance genes and suggests how bacteriophages can be used as an alternative to the current periodontal disease therapies.